Attitude and fear regarding death in older adult people - Martínez-Heredia, Nazaret (Empiria. Revista de metodología de ciencias sociales, 2021)
Death has often been considered a taboo subject in many societies over time. Over the years, our Western culture in Spain has set aside the issue of death through its avoidance or even denial, removing it little by little from our environment, avoiding it as an evil that threatens us. In the same way, we currently see how the quality of life increases along with a higher life expectancy at around 80. Through this article we intend to reflect about attitudes towards death in older adult people, both at group and individual level. To a qualitative methodological design was selected using an information collecting technique, and a semi-structured and in-depth interview to look into the life story of the older adult. The survey consisted of interviews with 30 individuals from the city of Granada (Spain) aged 65 to 85. The results indicated a positive attitude to death of oneself but not so much to the death of others, expressing the fear or the anxiety towards the finiteness of a loved one. The main conclusion is the need for creating educational spaces aimed at adults, to be able to treat these negative attitudes and reinforce the positive ones through the development of pedagogy and education regarding death. La muerte ha solido ser considerada a lo largo del tiempo como un tema tabú en múltiples sociedades. A lo largo de los años, nuestra cultura occidental en España ha apartado el tema de la muerte a través de su evitación o incluso negación, retirándola poco a poco de nuestro entorno, evitándola como un mal que nos amenaza. Del mismo modo, actualmente vemos cómo la calidad de vida aumenta junto con una mayor esperanza de vida situándose en torno a los 80. A través de este artículo, nos proponemos reflexionar sobre las actitudes hacia la muerte en las personas mayores, tanto a nivel grupal como individual. En este artículo se desarrolló un diseño metodológico cualitativo mediante la utilización de la entrevista semiestructurada y en profundidad como medio de recogida de información. La muestra está formada por 30 personas de la ciudad de Granada (España) de 65 a 85 años. Los resultados indicaron una actitud positiva hacia la muerte de uno mismo, pero no tanto hasta la muerte de otros, expresando el miedo o la ansiedad hacia la finitud de un ser querido. La principal conclusión muestra la necesidad de crear espacios educativos dirigidos a mayores, para poder tratar estas actitudes negativas y reforzar las positivas a través del desarrollo de la pedagogía y la educación con respecto a la muerte.